3D gamma analysis between treatment plans for nominally beam‐matched medical linear accelerators using PyMedPhys - Fada Guan; William Donahue; Simon Biggs; Matthew Jennings; Emily Draeger; Huixiao Chen; Yuenan Wang; Ngoc Nguyen; David J. Carlson; Zhe Chen; Dae Yup Han (Precision Radiation Oncology)
Abstract Beam‐matched linear accelerators (linacs) enable flexible patient scheduling and efficient treatment delivery in the event of unexpected machine downtime. The purpose of this study was to test the feasibility of 3D gamma index as an additional metric beyond standard measurement‐based comparisons for more efficient evaluation of treatment plans between linacs with nominally matched beam models to ensure safe patient transfer. Seventeen 3D conformal radiotherapy (3DCRT) plans and thirty‐six volumetric‐modulated radiation therapy (VMAT) plans for different disease sites were selected from the original linac. An in‐house script was used to automatically create new plans for the target linac and calculate dose using parameters of the original plans. 3D gamma analysis was performed to compare plan dose distributions between the target and original linacs using PyMedPhys. The 2%/2 mm gamma pass (γ≤1) rate was >99.99% for all 3DCRT plans. The median 1%/1 mm pass rate was 99.86% but two cases failed (< 90%). For VMAT plans, the median and minimum 2%/2 mm gamma pass rates were 99.43% and 93.81%. For 1%/1 mm, the median pass rate was 92.02% but ten cases failed. The results indicated using 3D gamma index can enhance the confidence and add an extra layer for safe patient transfer.